Pengaruh Fasilitas Wisata Terhadap Kepuasan Pengunjung di Daya Tarik Wisata Buper Guak Lago Kabupaten Lima Puluh Kota - Gavi Rahmat Pratama; Ira Meirina Chair (JURNAL KAJIAN PARIWISATA DAN BISNIS PERHOTELAN, 2023)
The background of the research is that there are several phenomena regarding visitor satisfaction and complaints about existing facilities. The purpose of this study was to see the effect of tourist facilities on visitor satisfaction at Buper Guak Lago. This is associative research with a survey method. The population in this study were visitors who had visited in the last 6 months, with a sample size of 70 people. Collecting research data with an adapted questionnaire that has gone through valid and reliable tests. Data analysis using linear regression analysis. In the results of research on 70 samples, Tourist Facilities (X) as a whole 50% in the good category. Visitor Satisfaction (Y) as a whole shows a percentage of 31.4% in the good enough category. It can be concluded that the results of the regression test, simple linear number f count 26.571 with sig 0.000 <0.05 regression model, can be used. This means that the Tourist Attraction Facility variable (X) has an effect on. the visitor satisfaction variable (Y) then Ha is accepted and Ho is rejected. And the results of the coefficient of determination test obtained R square 0.281 which means that the Tourist Object Facility (X) and Visitor Satisfaction (Y) are 28.1% while 71.9% is influenced by other factors